Refractive and visual outcome of toric intraocular lens implantation following cataract surgery - Ale, JB; Power, J; Zohs, K; Cunningham, F (Nepalese Journal of Ophthalmology, 2012)
Purpose: To evaluate the refractive and visual outcome of toric IOL implantation for correction of pre-existing corneal astigmatism following cataract surgery. Materials and methods: In this retrospective study, 56 eyes of 30 patients who underwent implantation of toric IOL following regular phacoemulsification were divided into two groups based on the types of toric IOL implanted: group 1 patients received Acrysof toric (Alcon) and group 2 patients received AT-Torbi (Zeiss Meditech) IOLs. Pre-and post-operative corneal and refractive astigmatisms, and post-operative distance vision were investigated. Statistical analysis was carried out using the paired student t-test when necessary. Factors affecting the success of toric IOL implantation are discussed and recommendations are made to optimize the outcome. Results: The mean age of all patients was 75.56 ± 9.87 years. No statistical difference was observed between pre-and post-operative corneal astigmatism (p = 0.819). Postoperative refractive astigmatism was significantly less in both groups (Group 1: p = 0.0014; Group 2: p=